Two Asias : the emerging postcrisis divide - Rosefielde, Steven; Kuboniwa, Masaaki, 1949-; Mizobata, Satoshi, 1955- (World Scientific, 2012)
Two Asias provides a fresh perspective on the Asia's disparate economic prospects in the wake of the 2008 global financial crisis and the Great Recession. The financial crisis, its propagation and real economic consequences are carefully documented, and used in conjunction with prior trends to identify the impending reconfiguration of wealth and power in Asia, and between Asia and the developed west. The study highlights Asia's cultural and systemic diversity, and suggests that China's, Vietnam's and South Korea's extraordinary catch-up during the last two decades is on the cusp of fading due.